1993
DOI: 10.1677/joe.0.1380307
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mRNA coding for pituitary hormones and pituitary-specific transcription factor in the pituitary gland of the rdw rat with hereditary dwarfism

Abstract: The rdw rat (gene symbol: rdw) with hereditary dwarfism has been shown immunohistochemically to have subnormal numbers not only of GH- but also of prolactin- and thyrotrophin-positive cells. To characterize the dwarfism of this strain, the expression of pituitary hormone mRNAs was examined by Northern hybridization. The pituitary gland in the rdw rat expressed 30-100 times less GH and prolactin mRNAs than normal controls, whereas mRNAs for pro-opiomelanocortin and the alpha subunit of rat glycoprotein hormone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 24 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…Shibayama et al reported a spontaneous dwarf rat originating from a Wistar Imamichi closed colony [23]. Suzuki et al reported a novel gene of rat dwarfism from Wistar Imamichi rats [25].…”
Section: Discussionmentioning
confidence: 99%
“…Shibayama et al reported a spontaneous dwarf rat originating from a Wistar Imamichi closed colony [23]. Suzuki et al reported a novel gene of rat dwarfism from Wistar Imamichi rats [25].…”
Section: Discussionmentioning
confidence: 99%
“…In the rdw rat, the thyroxine (T 4 ) levels in serum are drastically decreased [19,21,23], but the thyroid-stimu-…”
Section: Abstract: Growth Rdw Rat Thyroid Therapymentioning
confidence: 99%
“…Rat Pit-1 cDNA (826 bp) corresponding to nucleotides 104 to 928 [10] was prepared. Rat TSHβ cDNA was made by the RT-PCR method using poly (A)+ RNA prepared from normal rat pituitaries as the template and cloned into pUC118 [21]. Human glyceraldehyde-3 phosphate dehydrogenase (G3PDH) cDNA was obtained from Clontech (Palo Alto, CA, USA).…”
Section: Probesmentioning
confidence: 99%
See 2 more Smart Citations